The relationship between stunting and caries status in children aged 3-5 years in Parangloe District, Gowa Regency in 2021: Hubungan stunting dengan status karies pada anak usia 3-5 tahun di Kecamatan Parangloe Kabupaten Gowa tahun 2021 - Sari Aldilawati; Sitti Fadhillah Oemar Mattalitti; Anisa Anastasya (Makassar Dental Journal PDGI Makassar, 2023)
Stunting is a chronic condition that describes the inhibition of child growth due to long-term malnutrition. This condition is an advanced manifestation of the high of low birth weight (LBW) and malnutrition during toddlerhood. One of the causes of child stunting is malnutrition; while good nutrition is necessary for health. Nutrition also plays an important role in the development and defense of oral health, especially teeth and gingiva. The condition of healthy or unhealthy teeth and gingiva can affect child-ren's food intake because children who are malnourished will have an increased risk of high caries due to reduced salivary func-tion as a buffer, cleanser, and antibacterial in the oral cavity. The study discussed the relationship between stunting and caries sta-tus in children aged 3-5 years in Parangloe District, Gowa Regency. Analytic observational study with cross sectional design using hard file questionnaire. Data were tested using Pearson correlation. The sample consisted of stunted children recorded at the Parangloe Health Center in 2021, as many as 30 respondents, showing a p-value coefficient of 0.047 (p<0.05) which means there is a significant relationship. It is concluded that there is a relationship between stunting and caries status in children aged 3-5 years in Parangloe District, Gowa Regency in 2021.